Sustainability of Southern African Ecosystems under Global Change Science for Management and Policy Interventions - von Maltitz, Graham P.; Midgley, Guy F.; Veitch, Jennifer; Brümmer, Christian; Rötter, Reimund P.; Viehberg, Finn A.; Veste, Maik (Ecological Studies, 2024)
This open access book about the sustainability of marine and terrestrial ecosystems in southern Africa provides a synthesis of the research program Science Partnerships for the Adaptation to Complex Earth System Processes (SPACES II, 2018-2022). It addresses the scientific, social, and economic issues related to climate change, its potential impacts on the various ecosystems, adaptations, and management interventions for enhancing systems resilience in Southern Africa. It is written by numerous scientists from African states and Germany and summarizes the latest research findings, which are of great relevance for a better understanding of climate change impacts, adaptations, and vulnerabilities as well as for developing management options and policy options to reduce the associated risks. This is crucial considering that the projected African population increase is exceptional. Furthermore, climate change is assumed to hit southern Africa extremely hard with a significant increase in extreme events and the frequency of severe droughts, heat waves, and flooding. Southern Africa hosts a high variety of ecosystems, which belongs to important biodiversity hotspots for unique flora and fauna. The surrounding oceans form, in turn, a bottle neck within the ocean's global thermohaline circulation, act as a still poorly understood carbon sink and source and play an important role for fisheries as they are highly productive. Considering these important aspects, the book is an important interdisciplinary contribution to the scientific literature and will find a wide readership. The book is aimed at students, teachers, and scientists in the fields of terrestrial and marine ecology, environmental, nature and landscape planning, agriculture, environmental and resource management, biodiversity, and nature conservation, as well as scientists and representatives in specialised authorities and associations, nature conservationists, and policy makers of related disciplines.